Effect of Interactive Marketing and Electronic Word of Mouth on Brand Awareness of Skintific Products - Mela Arimbi; Seno Aji Wahyono; Kalimasada (Indonesian Journal of Business Analytics, 2023)
With the more intense business competition in the world of beauty, of course, every brand needs an effective strategy to increase consumer buying interest. One of the newly entered skincare brands in Indonesia is a Skintific skincare brand from Canada. The purpose of this study was to determine the effect of interactive marketing and electronic word of mouth on brand awareness of Skintific products. The type of research used is quantitative research with the Google form questionnaire distribution method. The sample in this study was 100 respondents using the SPSS program. The classic assumption tests used in this study are normality, homoscedasticity, non-multicollinearity, and linearity. Then after testing the classical assumptions, it can be concluded that the results of interactive marketing and electronic word-of-mouth variables have a positive effect on brand awareness of Skintific products.